Inspecting pollution emit from vehicle & controlling speed of vehicle using IOT - Murugeswari, D; Malathi, R; Narmadha, D; Sireesha, K (International Journal of Engineering and Technology, 2018)
At present the number of people using the vehicle is increased tremendously. Therefore the pollution such as air & noise emitted by the vehicle is also increases proportionally. 1] Air is polluted with hazardous gases emitted by motor vehicles. This polluted air is adversely affects the health of humans, animals, birds and the growth of trees. 2] Sometimes horn sound raised by the vehicles, near to the hospital, school and college zones makes unpleasure to the folks over there. 3] The drivers drive vehicles at high speed even in speed restricted areas without considering the safety of the public. To overcome the above stated problems this paper presents the way for controlling the air & noise pollution emitted by the vehicle by using the sensor & IoT Technologies and speed of the vehicle is also controlled in school, hospital and college zones to avoid accidents for some extent.Â Â